Reactivity of fatty acid methyl esters under atmospheric pressure plasma jet exposure: An experimental and theoretical study. Issue 10 (24th April 2017) - Martini, Luca Matteo; Maranzana, Andrea; Tonachini, Glauco; Bortolotti, Giulia; Scapinello, Marco; Scotoni, Mario; Guella, Graziano; Dilecce, Giorgio; Tosi, Paolo
Abstract : We have investigated the treatment of a mixture of fatty acid methyl esters by an RF‐plasma jet with He‐H2 O and He‐O2 gas feed. We have measured the concentration of the hydroxyl radical in the jet by laser induced fluorescence, looking for correlation with the lipid reactivity. We have detected four product families, whose yields increase with the OH exposure: volatile products, polymerization products, reduced chains, and oxidized chains. Theoretical calculations give insights on the radical attack to the lipid chain and show that none of the products can be attributed exclusively to reactions with OH. Therefore, the observed reactant conversion as function of the OH exposure must be interpreted as a qualitative relationship with the total amount of radical species present in the plasma jet. PACS : 52.80.Tn, 82.33.Xj, 31.15.E‐. Abstract : The interaction of radicals with lipids is of paramount importance in different fields ranging from biology to atmospheric chemistry . Fatty acid methyl esters are treated by a plasma jet, while laser induced fluorescence is used to measure the concentration of the hydroxyl radical in the jet, as a partial characterization of the flux of radicals that induce the lipid reactivity. Theoretical calculations give some hints on the reaction mechanisms.